2002
DOI: 10.1093/fampra/19.5.476
|View full text |Cite
|
Sign up to set email alerts
|

Patient trust in the physician: relationship to patient requests

Abstract: Patients with a lower level of trust in their physician are more likely to report that requested or needed services are not provided. Understanding this relationship may lead to better ways of responding to patient requests that preserve or enhance patient trust, leading to better outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
255
0
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(274 citation statements)
references
References 8 publications
9
255
0
10
Order By: Relevance
“…Previous research has found that referral and monitoring by health professionals tends to increase trust, 47 whereas lack of trust in health professionals leads to greater dissatisfaction with services. 48 However, those who did not wish to visit their GP for their insomnia also wanted to be able to access CCBT-I directly.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Previous research has found that referral and monitoring by health professionals tends to increase trust, 47 whereas lack of trust in health professionals leads to greater dissatisfaction with services. 48 However, those who did not wish to visit their GP for their insomnia also wanted to be able to access CCBT-I directly.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…It is important in its own right and it mediates other positive outcomes, including adherence to treatment. 1 Recent changes to the organisation and delivery of primary care in the UK have the potential to reduce continuity of care markedly, 2 as patients are increasingly likely to be consulting unfamiliar health professionals. It is not clear how this will have an impact on patient trust.…”
Section: Introductionmentioning
confidence: 99%
“…Zaupanje pripomore k oblikovanju kakovostnega odnosa med zdravnikom in bolnikom, povezano je z boljšim izidom, kontinuiteto zdravljenja, sodelovanjem in zadovoljstvom bolnika (1)(2)(3)(4) ter naj bi bilo povezano tudi s placebo efektom (5). Gre za ključno komponento odnosa, kjer osebi druga drugi verjameta, da sta dobronamerni, kompetentni in pripravljeni ravnati na zaželeni in/ali dogovorjeni način (1,6).…”
Section: Uvodunclassified
“…Enako so potrjevale tudi tuje raziskave (3,7,11,14), kar pomeni, da IzvIrnI znanStvenI članek povezave med izobrazbo bolnika in zaupanjem v zdravnika (17). Prisotna kronična bolezen ni bila statistično povezana z zaupanjem (Tabela 2), kar se večinoma ujema s tujimi študi-jami (3,11). Zanimivi so rezultati Fiscellove raziskave, v kateri so bile določene bolezni, kot npr.…”
Section: Razpravljanjeunclassified
See 1 more Smart Citation